Perlindungan Privasi Pejabat Publik berdasarkan Undang-Undang No. 14 Tahun 2008 Tentang Keterbukaan Informasi Publik Perspektif Siyāsah Dustūriyyah - Syahputra, Zailani; Putriekaramadhani (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the principle of public officials’ privacy protection from the perspective of siyāsah dustūriyyah, focusing on the balance between the right to public information and the individual’s right to privacy. The research employs a qualitative approach with a juridical-normative type of study. It integrates the analysis of legal norms contained in Law Number 14 of 2008 on Public Information Disclosure with the Islamic constitutional political concept of siyāsah dustūriyyah. The statute approach is applied to examine the legal provisions governing the boundaries of openness and privacy protection, and the conceptual approach to explore the concepts of sitr (protection of honor), maṣlaḥah (public interest), and information ethics in Islamic governance. The findings indicate that transparency serves as a form of public accountability that must be implemented proportionally without violating officials’ privacy rights. From the siyāsah dustūriyyah perspective, protecting the privacy of public officials constitutes an effort to uphold human dignity and a manifestation of justice and public welfare within a civilized Islamic governance framework.